DZIELIMY SIĘ DOŚWIADCZENIEMMyocardial rupture in patients with acute ST-elevation myocardial infarction. The role of surgical treatment - Ptaszyńska-Kopczyńska, Katarzyna; Sobolewska, Dominika; Kożuch, Marcin; Dobrzycki, Sławomir; Sobkowicz, Bożena; Hirnle, Tomasz; J. Musiał, Włodzimierz; Kamiński, Karol (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction: Heart rupture is one of the important causes of patients’ death in the acute phase of myocardial infarction. Early diagnosis of heart rupture can be based on echocardiography, which may enable cardiosurgical treatment that gives patients the best survival chances. Aim of study : The goal of the study was to analyse the changes in treatment of patients with heart rupture in the last decade. Also the diagnostic importance of electrocardiography was assessed. Material and methods : Fifty-five patients with cardiac rupture were selected out of patients with acute myocardial infarction with ST elevation (STEMI) hospitalized from 1996 to 2007. Free wall or ventricular septal rupture was diagnosed in echocardiography or autopsy. The selected population was divided into two groups (before and since 2004) based on availability of surgical treatment. Students’ t-test and Chi2 test were used in statistical analysis. Results: Primary coronary angioplasty was performed in 32 (58.2%) cases, including 27 (84.4%) patients hospitalized since 2004. Half of the group hospitalized since 2004 had cardiosurgical treatment. In the population hospitalized since 2004, the subpopulation with cardiosurgical treatment had lower mortality (31.3%) than the group with conservative treatment (81.3%). Suture of the rupture was performed during 3 operations, whereas a patch was used six times. The main symptom in echocardiography was the presence of fluid in the pericardial sac. Conclusions : Invasive treatment of myocardial infarction and cardiosurgical intervention in the case of heart rupture improve patients’ chances of survival. Routine bedside echocardiography increases the frequency of diagnosed rupture and enables cardiosurgical treatment.